2013
DOI: 10.1534/genetics.112.144402
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Silkworms for Resistance to Baculovirus Through Multigene RNA Interference

Abstract: Bombyx mori nucleopolyhedrovirus (BmNPV) that infects the silkworm, B. mori, accounts for .50% of silk cocoon crop losses globally. We speculated that simultaneous targeting of several BmNPV essential genes in transgenic silkworm would elicit a stable defense against the virus. We introduced into the silkworm germline the vectors carrying short sequences of four essential BmNPV genes in tandem, either in sense or antisense or in inverted-repeat arrangement. The transgenic silkworms carrying the inverted repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…Although one target site for the ie-1 gene abolished genomic cleavage because of a single-nucleotide mismatch between the gRNA template and its BmNPV genome target, our data showed that the remaining three target sites were sufficient to introduce large-segment deletions into BmNPV genomes and the relative abundance of BmNPV was decreased to a nearly undetectable level (>10 4 -fold) in TG silkworms (Fig. 4), which was quite different from the limited viral blockage (2.5- to ∼16.7-fold) achieved by RNAi-based antiviral strategies (8, 9). The markedly enhanced survival of the engineered silkworms supports the BmNPV-specific CRISPR/Cas9 system as a promising tool for application in sericulture.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Although one target site for the ie-1 gene abolished genomic cleavage because of a single-nucleotide mismatch between the gRNA template and its BmNPV genome target, our data showed that the remaining three target sites were sufficient to introduce large-segment deletions into BmNPV genomes and the relative abundance of BmNPV was decreased to a nearly undetectable level (>10 4 -fold) in TG silkworms (Fig. 4), which was quite different from the limited viral blockage (2.5- to ∼16.7-fold) achieved by RNAi-based antiviral strategies (8, 9). The markedly enhanced survival of the engineered silkworms supports the BmNPV-specific CRISPR/Cas9 system as a promising tool for application in sericulture.…”
Section: Discussionmentioning
confidence: 59%
“…Total DNA was extracted from silkworms treated with 10 6 OBs/larva in the TG-A, TG-B, TG-C, and WT groups every 12 h (from 0 to 72 hpi). Several BmNPV genes, including lef-1 , lef-3 , gp41 , and gp64 , were used in previous studies for viral DNA quantification (8, 9, 28). Among them, the lef-3 and gp64 genes, two essential genes beyond the range of the gRNA target deletion sequences, were selected as the detection indicators in quantitative PCR (qPCR) analyses of the relative abundance of BmNPV with Bmrp49 as the internal reference gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…piggyBac gene vectors are able to carry large fragments of exogenous DNA into genomes. In B. mori, the largest fragment integrated using a piggyBac vector was 12.4 kb [18]. Ma et al [13] reported that fragments 2-8 kb in length had no significant effect on the transformation efficiency of B. mori using piggyBac vectors.…”
Section: Transposon-based Technologies (A) Transgene Integration Techmentioning
confidence: 99%
“…In contrast, agricultural systems can sometimes be engineered for disease resistance, as Subbaiah et al (2013) have shown by establishing stably transformed silkworms that are resistant to Bombyx mori nucleopolyhedrovirus (BmNPV). The transformed silkworms carry RNAi constructs that target four essential viral genes, generating .75% survival of experimental viral infection relative to ,15% survival in the parental strain.…”
Section: Agriculturally and Ecologically Relevant Systemsmentioning
confidence: 99%